(N{WEJNOE OBORUDOWANIE DLQ PROIZWODSTWA WERHNIH REGULQRNYH TRIKOTAVNYH IZDELIJ (B/s - (NaLEKSI[WILI(B, (NtATXQNA iWANOWNAs; (NbOGDASAROW(B, (NlEONID aFANASXEWI^s ((NmOSKWA (B:s (NlEGKAQ INDUSTRIQ(B,s, 1974)
(NbIBLIOGR(B. (NS(B. 182s
Keywords: (NtRIKOTAVNYE IZDELIQ (B- (N{WEJNOE OBORUDOWANIEs